THE INFLUENCE OF FLASH SALES AND CONSUMER TRUST ON PURCHASE DECISIONS OF SKINCARE BEAUTY PRODUCTS AT GUARDIAN STORE SURABAYA - Zaiza Fun Nabila; Is Fadhilah; Anis Fitriyasari (Pedagogic Research-Applied Literacy Journal, 2025)
This study aims to analyze the influence of flash sales and consumer trust on purchasing decisions for skincare beauty products at the Guardian Store Surabaya. With increasing public awareness of the importance of skincare, marketing strategies such as flash sales have become one way to attract consumers' attention. This study uses a quantitative approach with a survey method, where data is collected through questionnaires distributed to consumers who have purchased skincare products at the Guardian Store. The results of the analysis show that both flash sales and consumer trust have a significant positive influence on purchasing decisions. Flash sales create a sense of urgency that encourages consumers to make purchases immediately, while consumer trust in brands and products increases their likelihood of purchasing. These findings provide important insights for retailers in designing more effective marketing strategies, as well as emphasizing the importance of building trust in the beauty industry.